Peningkatan Literasi Ekonomi Syariah pada Para Siswa di SMA Muhammadiyah 3 Comal - Effendi, Bahtiar; Saifudin, Abdul Ghofar; Arisandi, Devy (CV Global Research Publication, 2025)
This community service program aims to improve sharia economic literacy among students of SMA Muhammadiyah 3 Comal. This activity was motivated by the low understanding of the younger generation of the basic principles of Islamic economics such as the prohibition of usury, gharar, and maisir, as well as the values of justice and social responsibility. This program targeted grade XI students and involved the Muhammadiyah Student Association (IPM) as part of the value dissemination strategy. The implementation method was carried out through a participatory and interactive approach in the form of lectures, group discussions, and sharia transaction simulations. The results of this program showed an increase in students' understanding of sharia economic concepts and a growing awareness to apply them in daily life. Participants showed high enthusiasm and encouraged schools to make this activity part of a sustainable program. This activity also has a positive impact on teachers and the school environment in developing sharia-based economic education.